Modelling and Experimental Verification of the Interaction in a Hydraulic Directional Control Valve Spool Pair - Michał Stosiak; Mykola Karpenko; Adam Deptuła; Kamil Urbanowicz; Paulius Skačkauskas; Rafał Cieślicki; Anna Małgorzata Deptuła (Applied Sciences, 2022)
This study examined the impact of mechanical oscillation on a hydraulic directional control valve. Particular attention was paid to the oscillating movement of the spool of the hydraulic directional control valve resulting from this impact. Different models of fluid and mixed friction were considered. The models analysed accounted for the relative movement of the directional control valve body and the fact that it is kinematically excited by external mechanical oscillations. It was observed that the mixed friction model, where the frictional force is considered to be the sum of molecular forces acting in micro-areas of contact and drag forces in the fluid, was the best for describing the movement of the spool for a specific spool oscillation frequency. This model yielded significantly more consistency between the simulated and experimental results than the classic fluid friction model.